Preference of Non-Muslim Customers towards Islamic Banks within Muslim Minority Areas in Indonesia - Hamzah Hamzah; Agus Yudiawan; St. Umrah (Share: Jurnal Ekonomi dan Keuangan Islam, 2023)
This study aims to explore the factors influencing the preferences of non-Muslim customers towards Islamic banks in Muslim minority areas in Indonesia. A quantitative approach was employed, with a sample of 232 non-Muslim customers participating as respondents. Data was collected using questionnaires administered directly to the participants and analyzed using exploratory factor analysis (CFA). The findings revealed four main preference factors: 1) access factors, encompassing variables related to facilities and location; 2) product quality factors, comprising variables pertaining to product, promotion, and reputation; 3) psychological factors, including variables of satisfaction, perception, and knowledge; and 4) socio-cultural factors, consisting of variables related to social status and religious status. These findings offer preliminary insights into the preferences of non-Muslim customers towards Islamic banks within Muslim minority areas in Indonesia. Further studies are warranted, particularly in non-Islamic countries aiming to establish Islamic banks. Moreover, future research can explore the formed variables using other analytical methods such as linear regression, discriminant analysis, or alternative analyses to deepen the understanding of Islamic banking development in Muslim minority regions. The outcomes of this study contribute valuable insights for Islamic banks to consider when developing banking services for non-Muslim customers, thereby promoting the growth of Islamic banking in Muslim minority areas. This research also adds to the existing literature on non-Muslim customer preferences in Islamic banks within Muslim minority areas.======================================================================================================== ABSTRAK – Preferensi Nasabah Non-Muslim terhadap Bank Syariah dalam Wilayah Minoritas Muslim di Indonesia. Penelitian ini bertujuan untuk mengeksplorasi faktor-faktor yang memengaruhi preferensi nasabah non-Muslim terhadap bank syariah dalam wilayah minoritas Muslim di Indonesia. Pendekatan kuantitatif digunakan dalam penelitian ini, dengan melibatkan sampel sebanyak 232 pelanggan non-Muslim sebagai responden. Pengumpulan data dilakukan melalui penggunaan kuesioner yang diberikan langsung kepada para responden, dan analisis dilakukan menggunakan metode analisis faktor eksploratori (CFA). Temuan penelitian ini mengungkapkan adanya empat faktor preferensi utama, yaitu: 1) faktor akses, yang meliputi variabel-variabel terkait fasilitas dan lokasi; 2) faktor kualitas produk, yang mencakup variabel-variabel terkait produk, promosi, dan reputasi; 3) faktor psikologis, yang melibatkan variabel-variabel kepuasan, persepsi, dan pengetahuan; dan 4) faktor sosial-budaya, yang terdiri dari variabel-variabel terkait status sosial dan status keagamaan. Temuan ini memberikan gambaran awal yang penting terkait preferensi nasabah non-Muslim terhadap bank syariah dalam wilayah minoritas Muslim di Indonesia. Untuk memperdalam pemahaman mengenai perkembangan perbankan syariah di wilayah minoritas Muslim, penelitian lanjutan perlu dilakukan, terutama di negara-negara non-Muslim yang berencana mendirikan bank syariah. Selain itu, penelitian selanjutnya dapat mengkaji permasalahan tersebut berbagai analisis lain, seperti regresi linear, analisis diskriminan, atau metode lainnya. Hasil penelitian ini berkontribusi dalam pengembangan layanan perbankan syariah untuk nasabah non-Muslim dan mendorong pertumbuhannya di daerah minoritas Muslim. Penelitian ini juga berkontribusi dalam memperkaya literatur terkait preferensi nasabah non-Muslim pada bank syariah di daerah minoritas Muslim.